Factors contributing to occupational injuries and ill health among healthcare workers in selected hospitals in Nairobi County - Koskei, Emily; Mburu, Charles; Nyamongo, Daniel (International Journal Of Community Medicine And Public Health, 2022)
Background: In the context of the highly complex and hazardous work environment, particular challenges arise in pursuing protections for healthcare workers in this unique employment sector. Due to its unique mission of caring for the sick, self-preservation behaviors which normally aid in protecting workers are suspended in a culture of selfless commitment to patient care. The objective of this study is to investigate factors influencing occupational injuries and hazards among healthcare workers in selected hospitals in Nairobi County. Methods: Descriptive cross-sectional study design was used. The scope included Kenyatta national hospital, Mama Lucy hospital, and Pumwani maternity hospital. A structured questionnaire and an observational checklist were used to collect information. A sample size of 304 healthcare workers was selected. Univariate and multivariate analysis was carried out to assess the association of study variables. Findings are presented in tables. Results: This research found that most of the healthcare workers (65.5%) are exposed to health hazards the commonest being cuts, wounds and lacerations (34.2%). The leading predisposing factors to health hazards are job related pressure (39.5%) and not wearing necessary PPEs (39.1%). There was a statistically significant relationship between experience of work-related injury and lack of enough supplies/materials and poor working environment (p<0.005). Conclusions: The study recommends that there should be much focus on creating awareness of occupational health hazards at the hospitals by the relevant stakeholders, preventive measures that will incorporate manageable workloads to reduce work-related pressure on the healthcare workers.